Representasi Identitas Gender Dan Seksualitas Tokoh Marginal Dalam Novel Rima Rima Tiga Jiwa Karya Akasa Dwipa: Kajian Teori Queer - Tiara Adenia; Prima Vidya Asteria (CV. SINAR HOWUHOWU, 2026)
Individuals with non-heteronormative gender identities and sexualities in Indonesia continue to face systemic social pressure through religious, legal, and media discourses. Akasa Dwipa's novel Rima Rima Tiga Jiwa presents three marginal characters Silvy (a waria), Susanto (bisexual), and Rima (a sex worker) whose representations will be examined using a queer theory framework. This study aims to analyze the construction of gender identity, synthesize the representation of sexuality, and critically examine forms of resistance to heteronormativity within the novel. The method employed is descriptive qualitative. The study was conducted through intensive reading of Rima Rima Tiga Jiwa as the primary data source. Data consist of words, phrases, sentences, and paragraphs representing the gender identity, sexuality, and resistance of marginal characters. Data analysis employed Judith Butler's gender performativity framework (1990) and Michel Foucault's notion of sexuality as a discursive product (1978). The study identified that gender identity is represented as an active construction built through language, the body, and early-life experiences, sexuality is represented as a product of power discourse that is never neutral, and resistance manifests in four complementary forms.